2019
DOI: 10.1111/lre.12288
|View full text |Cite
|
Sign up to set email alerts
|

Numerical expressions of otolith shape and morphometric relationships for five fish species in tidal‐linked lagoons in the northern Arabian Sea

Abstract: Otoliths from five fish species, including Acanthopagrus latus, Daysciaena albida, Ellochelon vaigiensis, Mugil cephalus and Mystus gulio, were used to develop numerical expressions involving otolith shape indices and morphometric parameters. A total of 342 fish specimens in lagoons (24°39′ 0N, 68°50′0E) were sampled from August 2014 to July 2015. A linear model related to fish sizes, otolith sizes and weights were applied, with estimated coefficients of determinations (r2 = 0.99–0.53). Otolith shape indices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…Furthermore, we reported that the relationship between otolith length × otolith weight for U. cirrosa was isometric, whereas a negative allometric growth pattern was respectively reported by Aneesh Kumar et al (2017) for opal fish Bembrops caudimacula, Indian ruff Psenopsis cyanea, Hoplostethus rubellopterus and blackspotted gurnard Pterygotrigla hemisticta from samples taken in the south-eastern Arabian Sea, India. The otolith width × otolith weight of U. cirrosa revealed a positive allometric growth, which agrees with the findings of Qamar et al (2019) for squaretail mullet Ellochelon vaigiensis and nuna tengra Mystus gulio. These authors also reported negative allometric growth in Acanthopagrus latus and Mugil cephalus, while reporting an isometric trend for assessments of Daysciaena albida from the northern Arabian Sea.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we reported that the relationship between otolith length × otolith weight for U. cirrosa was isometric, whereas a negative allometric growth pattern was respectively reported by Aneesh Kumar et al (2017) for opal fish Bembrops caudimacula, Indian ruff Psenopsis cyanea, Hoplostethus rubellopterus and blackspotted gurnard Pterygotrigla hemisticta from samples taken in the south-eastern Arabian Sea, India. The otolith width × otolith weight of U. cirrosa revealed a positive allometric growth, which agrees with the findings of Qamar et al (2019) for squaretail mullet Ellochelon vaigiensis and nuna tengra Mystus gulio. These authors also reported negative allometric growth in Acanthopagrus latus and Mugil cephalus, while reporting an isometric trend for assessments of Daysciaena albida from the northern Arabian Sea.…”
Section: Discussionsupporting
confidence: 89%
“…The otolith width × otolith weight of U. cirrosa revealed a positive allometric growth, which agrees with the findings of Qamar et al . (2019) for squaretail mullet Ellochelon vaigiensis and nuna tengra Mystus gulio . These authors also reported negative allometric growth in Acanthopagrus latus and Mugil cephalus , while reporting an isometric trend for assessments of Daysciaena albida from the northern Arabian Sea.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a positive allometric growth pattern was reported by some authors (Kanjuh et al, 2018;Uyan et al, 2019;Yılmaz et al, 2014). In the current study, the otolith perimeter-fish length relationship was negatively allometric, which agrees with the results of Qamar et al (2019) for three fish species. But, positive allometric growth was estimated for the relationship between the otolith area and fish length, which in contrast with the findings of Qamar et al (2019) for five fish species.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we reported that the relationship between otolith weight and fish length for S. coruhensis was negative allometric. This phenomenon was also observed for other fish species such as Acanthopagrus latus, Daysciaena albida, Ellochelon vaigiensis, Mugil cephalus, and Mystus gulio (Qamar et al, 2019). On the other hand, a positive allometric growth pattern was reported by some authors (Kanjuh et al, 2018;Uyan et al, 2019;Yılmaz et al, 2014).…”
Section: Discussionsupporting
confidence: 65%
“…These species migrate mainly in coastal waters but few enter the Indus River Estuary and are confined to freshwater channels. In addition to phenotypic characters, otolith shape and morphology are central to fish taxonomy and systematics (Qamar et al, 2019;Kashani and Panhwar, 2022). In typical bony fishes, the sagitta is usually the largest otolith but in the case of catfishes, the lapillus is the largest pair and is widely used for growth studies and species differentiation (Campana, 2004;Qamar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%